解方程:x2+1+x=6/x+x2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 02:35:51
解方程:x2+1+x=6/x+x2解方程:x2+1+x=6/x+x2解方程:x2+1+x=6/x+x2令x²+x=t原方程变为t+1=6/tt²+t-6=0(t+3)(t-2)=0
解方程:x2+1+x=6/x+x2
解方程:x2+1+x=6/x+x2
解方程:x2+1+x=6/x+x2
令x²+x=t
原方程变为
t+1=6/t
t²+t-6=0
(t+3)(t-2)=0
则t=2或-3
1)
x²+x=2
x²+x-2=0
(x+2)(x-1)=0
x=-2或x=1
2)
x²+x=-3
x²+x+1/4=-11/4
(x+1/2)²=-11/4
所以x无解
经检验x=-2或x=1是原方程的根
所以x=-2或x=1
解方程 2/(x2-x)+6/(1-x2)=7/(x2+x)x2为的平方
解方程x2-6/ x2-x=x-1
解方程:x2+1+x=6/x+x2
解方程:1/x2+x +1/x2+3x+2 +1/x2+5x+6 +1/x2+7x+12 +1/x2+9x+20=5/x2+11x-708解方程:1/x2+x +1/x2+3x+2 +1/x2+5x+6 +1/x2+7x+12 +1/x2+9x+20=5/x2+11x-708
(2x2+x+2)/(x2+x+1)+(x2+x+1)/(x2+1)=19/6解方程
解方程:X2--1/8(X2+2X)+X2+2X/3(X2--1)=11
解方程(x2+x+1)(x2+x+12)=42
解方程(x2+x)(x2+x-2)=-1
解方程x-4/x2+x-2=1/(x-1)+(x-6)/(x2-4)
方程7 / x2+x+ 3/ x2-x=6 / x2-x怎么解?
方程7 / x2+x+ 3/ x2-x=6 / x2-x怎么解?
解方程4x2-4x+1=x2+6x+9 7x2-√6x-5=0
解分式方程:1/(x2-2x-3) +2/(x2-x-6) +3/(x2+3x+2)=0
解分式方程:1/(x2-2x-3) +2/(x2-x-6) +3/(x2+3x+2)=0
3/x2=1/x2-x,解方程
x2+x2=(1-x)2,怎么解这个方程
解方程:1/x2+x +1/x2+3x+2 +1/x2+5x+6 +1/x2+7x+12 +1/x2+9x+20=5/x2+11x-708等会就要 再次坐等
解分式方程:2/x2+5x+6 + 3/x2+x-6=4/x2-4